Pemikiran Pendidikan Islam Multikultural Perspektif KH. M. Hasyim Asy’ari dan KH. Abdurrahman Wahid - Shidqi, Muhammad; Sodiqin, Muhdhor Muhammad; Miftah, Muhammad (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The racial, cultural, and religious diversity present in Indonesia poses its own challenges to the education system. Instead of being a source of division, these differences should be seen as an asset. This underscores the necessity of multicultural education. KH. Hasyim Asy'ari and KH. Abdurrahaman Wahid are two figures who have made significant contributions to the progress of Indonesia, particularly in the field of multicultural Islamic education. Therefore, it is important to examine the ideas of these two figures using qualitative methods and a literature review approach. The multicultural Islamic education they advocated has proven effective in addressing conflicts and divisions.